2017
DOI: 10.1111/ijcs.12383
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable older consumers: New persuasion knowledge achievement measure

Abstract: This research describes a new persuasion knowledge measure for older consumers which can be applied for both diagnostic and preventive purposes. Persuasion knowledge refers to information, attitudes, beliefs and schemas guiding our behaviour in situations where persuasion is involved. Many older consumers belong to a specific, vulnerable group, who often fail to maintain their interest in persuasive situations, so the proposed measure could serve a better understanding of their behaviour. First, a new, situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…These investigators also showed that consumers aged between 50 and 69 years are likely to spend more money and made online purchases more often than individuals aged between 18 and 25 years, whereas consumers aged over 70 years rarely make online purchases. However, elderly are not likely to look for information before purchasing, which can make them more vulnerable to frauds and scams (Bal azs et al, 2017). Thus, advertising messages targeting older consumers should contain information that helps alleviate concerns with security issues.…”
Section: Misleading Advertising and Fraudsmentioning
confidence: 99%
“…These investigators also showed that consumers aged between 50 and 69 years are likely to spend more money and made online purchases more often than individuals aged between 18 and 25 years, whereas consumers aged over 70 years rarely make online purchases. However, elderly are not likely to look for information before purchasing, which can make them more vulnerable to frauds and scams (Bal azs et al, 2017). Thus, advertising messages targeting older consumers should contain information that helps alleviate concerns with security issues.…”
Section: Misleading Advertising and Fraudsmentioning
confidence: 99%
“…Consumer vulnerability has been recognised as an interplay of person, individual traits and the context within which the older person lives (Baker et al, 2005;Balázs et al, 2017). Reflecting this definition, participants proposed that both intrinsic and extrinsic factors could render a person at risk of financial abuse.…”
Section: Defining and Naming Themesmentioning
confidence: 99%
“…We'll investigate the factual domains of "micro" and "macro" harmful products based on their producers, disadvantaged "secondary" passive consumers, and consequent consumer detriment (Berg, 2015;Balázs et al, 2017;Graham, 2018;Knobel, 2018).…”
Section: The "New" Vulnerable Consumersmentioning
confidence: 99%
“…There has been much interest among researchers regarding vulnerable consumers (Gellad et al, 2006;Timmermann, 2009;Wilson & Sheehan, 2009;Bartl, 2010;Garrett & Toumanoff, 2010;Harrison & Gray, 2010;Chan & Ghani, 2011;Wilson, 2012;Berg, 2015;Balázs et al, 2017;Knobel, 2018;Graham, 2018). The domain of "vulnerables" are primarily the poor and powerless who pay more (Caplovitz, 1963;Goodman, 1968;Hudson, 1993), the ethnically disadvantaged consumers (Andreasen 1975(Andreasen , 1982(Andreasen , 1993 and the ghetto communities (Sturdivant, 1969;Andreasen, 1997).…”
Section: Introductionmentioning
confidence: 99%